The numerical calculation of statically admissible slip-line field for plane strain compression of a three-layer symmetric strip between rigid plates - Thanh, Nguyen Manh; Nguyen, Kien Trung; Alexandrov, Sergei (Vietnam Journal of Science and Technology, 2021)
This paper present a method to build up statically admissible slip-line field (the field of characteristics) and, as a result, the field of statically admissible stresses of the compression of a three-layer symmetric strip consisting of two different rigid perfectly plastic materials between rough, parallel, rigid plates (for the case: the shear yield stress of the inner layer is greater than that of the outer layer). Under the conditions of sticking regime at bi-material interfaces and sliding occurs at rigid surfaces with maximum friction, the appropriate singularities on the boundary between the two materials have been assumed, then a standard numerical slip-line technique is supplemented with iterative procedure to calculate characteristic and stress fields that satisfy simultaneously the stress boundary conditions as well as the regime of sticking on the bi-material interfaces